PERLUASAN KEDUDUKAN DAN PERAN ALAT BUKTI PETUNJUK DALAM PEMBUKTIAN PERKARA PIDANA MENURUTPASAL 183 KUHAP - Dimas Dwi Aristia (VERITAS, 2018)
The judge shall not obtain such beliefs from any circumstances known from outside the proceedings. However, it must obtain from the evidence of valid evidence and additional evidence of evidence contained in the proceedings, in accordance with the conditions prescribed by law, in the event that the defendant does not recognize from or with any testimony at least, lack of two witnesses who have been lawfully sworn in the court.The research specification used is descriptive analysis. Descriptive because of the results of this study is expected to obtain a comprehensive and systematic picture of the extension of the position and the role of evidence evidence related to the issues raised in this study. Analytical because then from the results of research conducted an analysis of the problems of role extension and the position of evidence evidence.Legal Considerations The Constitutional Court Decision Number 20 / PUUXIV / 2016 has brought legal issues in the enforcement of cyber law in Indonesia, namely the annulment of Article 5 paragraph (1) and paragraph (2) which is considered to have no legal force and with the addition of Conditional Proof in the context of law enforcement on cyber cases, has hampered and weakened law enforcement in the imposition of criminal sanctions against perpetrators of cyber crime.